An Analysis between Eastern and Western Countries in Implementing Digital Literacy Skills for Young Learners - Dieni Nurhasanah Dwihastuti; Muchlas Suseno; Ifan Iskandar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2022)
AbstractTo face the global era, students in the twenty-first century must master the English language confidently and critically. One of the techniques for improving students' English language abilities is digital literacy. This research will look at how digital literacy is implemented to improve students' ability to master the English language and what challenges learners face when participating in these activities for elementary school students. It is an analysis based on the cultural characteristics of the western and eastern countries. The research methodology was content analysis. The writer gathered information by reading articles about the use of digital literacy in learning English. The findings verified some facts, such as the notion that using digital literacy in the classroom increases primary pupils' motivation for learning English. It also encourages students to learn new languages. Second, some children continue to have difficulty with digital literacy. Not to mention, some schools do not provide enough tools for students to apply digital literacy, which has an impact on classroom teaching and learning. However, further research on providing appropriate digital literacy based on kids' age or level of learning is required.Keywords: Eastern and Western countries, digital literacy, English language learning, young learner